Double-blind, randomized and controlled trial of EPI-743 in Friedreich's ataxia. (August 2018) - Zesiewicz, Theresa; Salemi, Jason L; Perlman, Susan; Sullivan, Kelly L; Shaw, Jessica D; Huang, Yangxin; Isaacs, Charles; Gooch, Clifton; Lynch, David R; Klein, Matthew B
Aim: To evaluate the safety and clinical effects of EPI-743 in Friedreich's ataxia patients. EPI-743 is a compound that targets oxidoreductase enzymes essential for redox control of metabolism.Methods: We conducted a multicenter trial that evaluated EPI-743 during a 6-month placebo-controlled phase, followed by an 18-month open-label phase. End points included low-contrast visual acuity and the Friedreich's Ataxia Rating Scale.Results/conclusion: EPI-743 was demonstrated to be safe and well tolerated. There were no significant improvements in key end points during the placebo phase. However, at 24 months, EPI-743 treatment was associated with a statistically significant improvement in neurological function and disease progression relative to a natural history cohort (p < 0.001).